Thermo-mechanical modeling and characterization of three-phase shape memory alloy hybrid composites. (1st December 2020) - Yu, Haifan; Lu, Linjun; Qiao, Pizhong
Abstract: The thermo-mechanical properties of shape memory alloy hybrid composites (SMAHCs) are characterized, and their three-phase constitutive relationship in the form of a lamina embedded with shape memory alloy (SMA) wires is established by micromechanics. Considering large beam deflection, a theoretical bending model of SMAHC beams with different fiber volume fractions and arbitrary ply schemes is proposed. The Runge–Kutta method is employed to solve the nonlinear ordinary differential equations, and the quantitative relations of curvature, rotation and deflection under thermal load are obtained from the model by directly using the original three-phase material parameters without the need of the experimental measurement in single layer. The SMAHC beams with different fiber orientation, number of layers, and volume fraction of SMA are fabricated, and their thermo-mechanical behavior is experimentally evaluated. Good agreements between the theoretical predictions and experimental results demonstrate that the proposed model is capable of predicting the thermo-mechanical behavior of three-phase SMAHC beams. The generic model developed can be used as an analytical tool in design analysis and optimization of SMAHC structures for effective shape, tracking, and vibration control.